Review of the article “Structure of the technical dissertation in a writing laboratory in a classroom on violence in transit” - Oliveira, Isaias Cardoso de; Gomes, Welliton Dias (Revista Coleta Científica, 2018)
This is a review article entitled "Technical dissertation structure in writing laboratory in classroom about traffic violence”. This article is authored by: Isaías Cardoso de Oliveira; Wellinton Dias Gomes. The article reviewed here was published in the periodical “Revista JRG de Estudos Acadêmicos”. Ano I, Vol. I, n.1, 2018.